Coping Mechanisms, Psychological Distress, and Quality of Life Prior to Cancer Genetic Counseling - Di Mattei, Valentina E.; Carnelli, Letizia; Bernardi, Martina; Bienati, Rebecca; Brombin, Chiara; Cugnata, Federica; Rabaiotti, Emanuela; Zambetti, Milvia; Sarno, Lucio; Candiani, Massimo; Gentilini, Oreste (Frontiers in Psychology, 2018)
Background: Breast Cancer susceptibility genes 1 and 2 are implicated in hereditary breast and ovarian cancer and women can test for the presence of these genes prior to developing cancer. The goal of this study is to examine psychological distress, quality of life, and active coping mechanisms in a sample of women during the pre-test stage, considering that pre-test distress can be an indicator of post-test distress. We also wanted to identify if subgroups of women, defined based on their health status, were more vulnerable to developing distress during the genetic counselling process. Methods: This study included 181 female participants who accessed a Cancer Genetic Counselling Clinic. Following a self-report questionnaire, a battery of tests was administered to examine psychological symptomatology, quality of life, and coping mechanisms. Results: The results confirm that the genetic counselling procedure is not a source of psychological distress. Certain participants were identified as being more vulnerable than others; in the pre-test phase, they reported on average higher levels of distress and lower quality of life. These participants were predominantly Ex-patients and Affected patients, who may be at risk of distress during the counselling process. Conclusions: These findings highlight that individuals who take part in the genetic counselling process are not all the same regarding pre-test psychological distress. Attention should be paid particularly to Ex-patients and Affected patients by the multidisciplinary treating team.